Observations on the performance of crossbred dairy cattle in smallholder herds in Degem District, Ethiopia - Dekeba, A.; Ayalew, W.; Hegde, B.P. (Ethiopian Society of Animal Production, 2004)
Overall performance of smallholder crossbred dairy herds was assessed by administering semi-structured questionnaires on 20 sample herds with crossbred and indigenous cattle in Degem. Reported average lactations yields of crossbreds were at least five times greater than that for indigenous cows; however, the data collected did not show the level of inputs used by the farmers, although it was generally expressed that crossbred cows were provided with greater amounts of supplementary feeds and veterinary inputs. Apart from the higher volume of milk production, crossbred cows by far greater estimated market prices, indicating higher inherent values attached to crossbreds than indigenous cows. However, there is lack of a reliable supply of breeding stock to sustain production of crossbreds on-farm; services of bull stations and AI services are declining; unintended and unknown genotype calves are produced. Trends in genetic change are not being monitored. Under these circumstances, the advantages with crossbred cows cannot be sustained. It was therefore concluded that the introduction of potentially more productive crossbred cattle in smallholder herds does not necessarily lead to genetic improvement.